'Africana womanism': Implications for transformative scholarship in occupational science. Issue 4 (2nd October 2018) - Huff, Stephanie; Rudman, Debbie Laliberte; Magalhães, Lilian; Lawson, Erica
ABSTRACT: This paper responds to the call for occupational scientists to advance understandings of occupation beyond a Western paradigm by considering the implications of drawing upon Africana womanism as a theoretical underpinning to explore gendered occupation. The uptake of Africana Womanist theory can challenge taken-for-granted assumptions tacitly embedded within occupational science surrounding gender and womanhood, while creating space for alternative ways of being, knowing, and doing in the conceptualization and study of occupation. The dual aims of this theoretical discussion paper are: to outline how Africana womanism both challenges implicit assumptions regarding gender and occupation (specifically gendered occupations) embedded in occupational science, and to critically consider how Africana womanism can advance understandings of occupation beyond a Western paradigm.